Revised Genome Sequence of Staphylococcus aureus Bacteriophage K - Gill, Jason J. (American Society for Microbiology, 2014)
Bacteriophage K is a member of the virulent Twort-like group of myophages infecting Staphylococcus aureus. The revised sequence presented here includes 12,436 bp of additional sequence not present in the previously available phage K genome (GenBank accession no. NC_005880) and updated annotations, and has been reopened at the predicted terminal repeat boundary.